Development of a Test Instrument for Students' Mathematics Learning Outcomes Oriented to Hots - Rahma, Dwi Fadillah (Lembaga Riset Mutiara Akbar, 2023)
Higher order thinking skills (HOTS) are high-level thinking abilities that involve more complex thinking processes in analyzing arguments, identifying, evaluating and developing critical, creative and analytical thinking skills. The development of test instruments for student learning outcomes can be seen from the level of difficulty of the questions as well as the validity and reliability of the test. A lesson is said to be successful if students master a concept, because the concept that has been understood will stick in the students' memory for a long period of time. Given the importance of mathematics, students are expected to discover and understand mathematical concepts. In mastering mathematical concepts, students must have high-level thinking skills. One way to find out whether students already have these skills is by conducting an assessment. Many studies show that students in Indonesia have low HOTS abilities compared to other countries.